Modelling the performance potential of forced and natural-draft biomass cookstoves using a hybrid Entropy-TOPSIS approach. (July 2021) - Boafo-Mensah, Gloria; Neba, Fabrice Abunde; Tornyeviadzi, Hoese M.; Seidu, Razak; Darkwa, Kwadwo Mensah; Kemausuor, Francis
Abstract: Improved biomass cookstoves have become significantly important as a major technological intervention to aid in the efficient use of biomass fuels. However, the transfer of such technologies to end users do not match the quantity of designs churned out to the market. This study therefore develops a new framework that simultaneously integrates technical, economic, social/public health and environmental factors in assessing the performance potential of biomass cookstoves. Experiments were conducted to determine 13 performance indicators of 20 (forced and natural draft) improved biomass cookstoves and application of the developed methodological framework indicated two main findings: (1) The forced draft cookstoves ranked better with technical and environmental factors while the natural draft cookstoves ranked better with economic and social/public health factors; (2) Considering all four performance indicators simultaneously, the natural draft cookstoves ranked better than the forced draft cookstoves. The results are of significant relevance to governments and organisations for identification of technological designs that should be improved or implemented from a sustainability perspective. Highlights: Renewable Energy technology selection is a multi-criteria decision-making process. Study develops a framework in assessing the performance potential of cookstoves. The framework combines Entropy and TOPIS methods for assessment of the cookstoves. Experiments were conducted to determine thirteen cookstoves performance indicators. Natural draft biomass cookstoves ranked best considering all performance indicators.